Survey: Recommender Systems, Techniques and New Trends - Khamael Raqim Raheem, Israa Hadi Ali (International Journal of Advanced Science and Technology, 2020)
Recommender systems play a vital role as they provide users with important, personalized data over the web. There is a critical range as of late showed up which is an affective recommender system. The affective recommender system is related to human behavior, mood, facial expressions, and body motions. For this combination and unique interests, more statement is required as compared to other ranges it is in awkward organizing and creating. So a literature survey has done within recommender systems techniques, feedback techniques, and affective recommender systems. Keywords: Recommender systems (RSs), Affective recommender systems (ARSs), Emotion.